Establecimiento de las líneas de investigación prioritarias en la didáctica de las ciencias y las matemáticas - Caballer Senabre, Mª Jesús; Carrascosa Alís, Jaime; Puig Espinosa, L. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
An attempt to find the research trends regarded as fundamental in science and mathematics education by the Teachers in this country is described. The results obtained in Biology, Physics and Chemistry and Mathematics are analyzed.